36 Cross regional collaboration to test protocol for the management of paediatric status epilepticus. (17th November 2016) - Quayle, Alexandra; Wilson, L; Farooq, O; Motaleb, F
Abstract : Background: Successful management of paediatric status epilepticus requires adherence to protocol with specific timing of treatment. Cohesive emergency team interaction with knowledge of best practice, equipment and good communication are vital. Our Development and Simulation Hub (DaSH) collaborating with paediatric leadership fellows from Health Education Yorkshire and Humber and School of Paediatrics tested the management at Scunthorpe and Grimsby hospitals in the Emergency departments (ED) followed by a joint interactive debrief. Methodology: Using a medium fidelity manikin we simulated a fitting 5 year old child in the ED. Responders were called initially with ED nursing and medical staff, paediatricians, and finally anaesthetic team. The child continued fitting, requiring timely treatment with benzodiazepines, phenytoin and finally anaesthesia and intubation. The team were observed for clinical assessment, knowledge and adherence to the protocol, equipment utilisation and team work. For a team to function effectively there must be a sense of collective responsibility. 1 Impact: Orchestrating in- situ simulation is challenging in resuscitation rooms. To minimise clinical impact we started early, relocating to an education room. The realism allowed us to detect and address the physical problems at each location eg. faulty lock, access to protocol. Revisiting later we ensured the latent risks were corrected. At Scunthorpe the cupboard lock had been replaced. At Grimsby the protocol is clearly visible in the paediatric bay. At two sites knowledge of the management protocol differed greatly. The facilitators comprised of DaSH staff, paediatric leadership fellows and experienced local clinicians. This mix was very effective in delivering feedback whilst maintaining local engagement. The visiting team reiterated key learning points from the scenario in other trusts. All team members felt improvement in knowledge 2 team working and addressing latent errors. Regional collaboration benefitted our organisation and we are now running regular paediatric simulations. References: World Health Organization. Being an effective team 2012.[online]. www.who.int/patientsafety/education/curriculum/course4_handout.pdf Eppich WJ, Adler MD, Mcgaghie WC. Emergency and critical care pediatrics:use of medical simulation for training in acute pediatric emergencies. Current Opinion in Pediatrics 2006 .18 (3):266–71